Suicidality Prevalence in a Pediatric Psychiatric Clinic: Relation to Social and Environmental Risk Factors - Stavroula Ilia; Evangelia Sakapeti; Panagiotis Briassoulis; George Gerostergios; Alexandros Vgontzas; George Briassoulis (MDPI AG, 2023)
Suicidality is a growing public health problem in children and adolescents. The aim of this retrospective data analysis study was to estimate the prevalence of suicidality in pediatric patients admitted to an academic Pediatric Psychiatric Clinic (PPC) and to analyze social and environmental risk factors associated with suicide. Suicidal ideation was assessed by the Self-Injurious Thoughts and Behaviors Interview. Using established psychometric scales, social and stressful events were analyzed. During the four-year study, 249 episodes of care were experienced by 152 individuals (mean age 15.2 ± 2 years, girls/boys 107/45). Twenty-eight patients (11.2%) were admitted from the Pediatric Intensive Care Unit and the Department of Pediatrics, 162 (65.1%) from the Pediatric Emergency Department, and 59 (23.7%) from other Hospitals (p = 0.003). A significant longitudinal increase in admissions to PPC, with increasing trends of suicidal ideation, suicide attempts, and suicidality, was recorded. Suicidal behavior, bullying, internet addiction, friends quarreling, and family problems were risk factors for suicide attempts and suicidality. Our results have implications for prevention programs, highlighting an increasing need for care for suicide attempts and suicidal ideation, related to specific stressful events and contextual socio-environmental status.